Remineralization of white spot lesions in orthodontic. Is that possible? Literature review - Maria Gabriela Acosta de Camargo; José Antonio Rodríguez; Hector Rodríguez (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2023)
Aim: The aim of this literature review is to describe the latest treatment available in the solution of this problem through remineralization. Literature review: A literature review was carried out in various electronic databases such as PubMed, MEDLINE, EBSCO, LILACS, EMBASE, Cochrane Library; from 1989 to 2022. The Medical Subject Headings (MeSH) terms used in the literature search were in English: "tooth reminaralization", "dental white spot", "orthodontic. Discussion: White spot lesions after orthodontic appliances is an undesired effect seen in dentistry. There is a wide option of agents that offer remineralization by the process of depositing calcium and phosphate ions into crystal voids in demineralized enamel, producing net mineral gain and preventing early enamel lesions progression, including fluoride toothpastes, fluoride varnishes, fluoride mouth rinses, and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP). Conclusion: Fluoride-based prevention strategies are the agent with the strongest evidence for the treatment of WSL. The dental professional should offer this therapy in the earliest phase of the lesions so that it can be remineralized.